Sagot :
✏️ Arithmetic Sequence
[tex] {\Large{\overline{\underline{\sf{\hookrightarrow Answer:}}}}} [/tex]
- [tex] \sf a_n = 5n - 4 [/tex]
Solution:
Given that:
- the first term [tex] \sf a_1 [/tex] = 1
- the common difference [tex] \sf d [/tex] = 5
✎ The common difference can be found by subtracting any term except the first term, by its preceding term. It is given by the formula [tex] \sf d = a_n - a_{n-1} [/tex].
Thus,
- [tex] \sf d = a_n - a_{n-1} \\ \sf d = a_2 - a_1 \\ \sf d = 6 - 1 \\ \sf d = 5 [/tex]
Solve using the formula for the general term of an arithmetic sequence:
[tex] {\large{\boxed{\sf{a_n = a_1 + (n-1)d}}}} [/tex]
- [tex] \sf{a_n = 1 + (n-1)5} [/tex]
- [tex] \sf{a_n = 1 + 5n - 5} [/tex]
- [tex] {\underline{\green{\sf{a_n = 5n - 4}}}} [/tex]
[tex]{\: \:}[/tex]
[tex] {\huge{\overline{\sf{Hope\:It\:Helps}}}} [/tex]
#LetsLearn #BeBrainly ✌☺